Examining the Use of Outdoor Learning for Visual Arts Education in the Irish Primary School - Skelly, Louise (Marino Institute of Education, 2021)
There is a long-standing history between Visual Arts and nature. Despite this very natural, collaborative, and synergetic relationship, whereby there are only gains from an arts and environmental education perspective, outdoor learning for the Visual Arts is being underutilised in Irish primary schools. This study explores and examines Irish primary school teachers’ perspectives and practices in relation to Visual Arts education and outdoor learning and aims to understand what are the barriers which create missed opportunities for both. In an era of curriculum reform in Ireland, this study aims to promote outdoor learning for Visual Arts and encourage its inclusion in the new Visual Arts Curriculum.